Spline methods for extracting interest rate curves from coupon bond prices - Daniel F. Waggoner (Federal Reserve Bank of Atlanta, 1997)
Cubic splines have long been used to extract the discount, yield, and forward rate curves from coupon bond data. McCulloch used regression splines to estimate the discount function, and, more recently, Fisher, Nychka, and Zervos used smoothed splines, with the roughness penalty selected by generalized cross-validation, to estimate the forward rate curve. I propose using a smoothed spline but with a roughness penalty that can vary across maturities, to estimate the forward rate curve. This method is tested against the methods of McCulloch and Fisher, Nychka, and Zervos using monthly bond data from 1970 through 1995.
Keywords: 330; Econometric models; Financial markets; Prices; Statistics